Proses Perencanaan Dan Penganggaran Keuangan Desa: (Studi di Kelurahan Banjaroyo Kabupaten Kulon Progo) - Daniswara Nursyahbani; Vara Tiska Luthfia DPS; Herlina Manurung (AKUNTANSI 45, 2023)
This study used qualitative descriptive research with the aim of describing the conditions of village financial planning and budgeting methods in Banjaroyo Village, Kalibawang District, Kulon Progo Regency. Those who provided information in this study were the village head, the Kalibawang sub-district empowerment village community, and representatives from the local community. The accumulated data used went through a process of observation, in-depth interviews and documentation. The results of this study prove that village planning and village financial budgeting have been proven by ongoing regulations. In terms of timeliness, there was a delay in determining the regional government work plan and village revenue and expenditure budget due to delays in the lack of quality human resources and the problem of delays in regulations from the district being conveyed to the village head.